(untitled) (European Journal of Behavioral Sciences, 2021)
Perceptions of mental health are often influenced by religious, sociopolitical and cultural beliefs, as well as differing views, values and attitudes towards the medical model of diagnosis, the potential causes of mental health disorders, and the approaches to mental health treatment and management. Six percent of the population of Indonesia, the fourth most populous nation in the world, struggle with mental illness. With strained mental health systems, pathways to improved mental health are further complicated by stigmatizing perceptions of mental illness and a significant lack of mental health literacy. These differing levels of mental health literacy in turn act to prompt help-seeking behaviours towards mental health services and treatment. The current article aims to explore the different perceptions towards mental illness and the levels of mental health literacy among Indonesians from research literature of the past twenty years. By garnering a wider understanding of the aspects that contribute towards the perceptions of mental health, researchers may be better equipped to improve and develop approaches towards increasing mental health literacy and improving mental health related help seeking behaviours of the overall Indonesian population.